2023
DOI: 10.1109/access.2023.3268763
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharge Detection by Edge Computing

Abstract: Edge computing is becoming a mainstream platform for practical applications of machine learning and in particular deep learning. Many systems capable of efficient execution of deep neural models in the context of edge computing are readily available or beginning to appear on the consumer market. The Jetson platform from NVIDIA, the Neural stick from Intel, and the Edge TPU designed by Google are examples of devices that enable the application of complex neural networks in edge computing. This work investigates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…This assertion is supported by our prior research, which also employed the ensemble technique with simpler models [37,38]. Furthermore, our preliminary assessments revealed that our two methods accurately identify different samples, thus exhibiting complementary behavior.…”
Section: Stacking Ensemblesupporting
confidence: 81%
“…This assertion is supported by our prior research, which also employed the ensemble technique with simpler models [37,38]. Furthermore, our preliminary assessments revealed that our two methods accurately identify different samples, thus exhibiting complementary behavior.…”
Section: Stacking Ensemblesupporting
confidence: 81%